Melvin Beederman, superhero : The fake cape caper - Trine, Greg.; Montijo, Rhode (New York : Henry Holt, 2007)
Melvin Breederman, superhero in charge of Los Angeles, attends the Superhero's Convention in Las Vegas, leaving his young sidekick to keep Los Angeles safe from evil bad guys and bullies.
640L
Accelerated Reader AR
Keywords: Heroes -- Fiction; Humorous stories; Los Angeles (Calif.) -- Fiction; Fiction